UNDERSTANDING THE CONCEPT OF NUMBER IN GRAMMAR ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
The article "The Category of Numbers in Linguistics" provides a comprehensive overview of how the grammatical category of number operates across various languages. It covers the essential distinctions between singular, plural, and dual forms, detailing how number is marked on nouns, pronouns, adjectives, and even verbs in different linguistic traditions. It explores languages that exhibit complex number systems, including those with dual forms, inclusive/exclusive plurals, and classifier systems, highlighting how number influences agreement within sentences. The article also addresses languages where number marking is minimal or context-dependent, such as in Chinese and Vietnamese. The article further examines how non-Indo-European languages and contact languages like pidgins and creoles may simplify or alter traditional number distinctions. It introduces the concept of number's role in categorizing entities, adding another layer of meaning to communication. The discussion of inclusive and exclusive plurals in languages like Fijian adds nuance to the ways communities structure and represent collective versus individual identities. In conclusion, the article stresses the importance of understanding number as a fundamental aspect of grammar that shapes communication, revealing both structural linguistic patterns and cultural perspectives. This resource is valuable for anyone interested in the diverse ways languages reflect human cognition and social organization through the lens of grammatical number.